New (other?) directions in corporate social responsibility - Nicholas Capaldi (International Journal of Corporate Social Responsibility (JCSR), 2016)
The purpose of this article is to challenge scholars of corporate social responsibility and CSR officers of private corporations to rethink their subject matter and their approach. The fundamental problem that needs to be addressed in CSR scholarship is whether it is descriptive or normative or something else. I maintain that much of the current literature is inadequately descriptive and philosophically deficient with regard to norms. I suggest a number of additional activities for CSR research (e.g., consumer responsibility) compatible with a morally pluralistic world that is hospitable to a market economy.
Keywords: 650